Development and Evaluation of a LiFi-Transceiver Module for TMTC Intra-Satellite Communication - Marek Jahnke; Benjamin Palmer; Ulf Kulau (Engineering Proceedings)
The use of Light Fidelity (LiFi) can enable the reduction of satellite mass by reducing the wiring harness while avoiding electromagnetic interference. In this paper, a LiFi-transceiver suitable for Telemetry and Telecommand (TMTC) intra-satellite communication is developed and evaluated. The focus of the implementation is on miniaturization and energy-efficiency. First test results with a simple Transimpedance-Amplifier and an investigation of the achievable eff. data rate depending on different distances and Error-Correcting-Codes and the energy-consumption of the developed transceiver are presented. The results show that the LiFi-transceiver achieves a payload data rate of 77.6 kbit/s with Error-Correcting-Code protection and thus can be used for a reliable TMTC communication within the satellite bus.